2010
DOI: 10.1016/j.neuint.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Glia as transmitter sources and sensors in health and disease

Abstract: Glial cells express a bewildering array of neurotransmitter receptors. To illustrate the complexity of expression, we have assayed non-glutamatergic neurotransmitter receptor mRNA in isolated rat optic nerve, a preparation devoid of neurons and neuronal synapses and from which relatively pure "glial" RNA can be isolated. Of the 44 receptor subunits examined which span the GABA-A, nicotinic, adreno-and glycine receptor families, over three quarters were robustly expressed in this mixed population of white matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 86 publications
0
30
0
Order By: Relevance
“…In a recent study, Fern and colleagues found that mRNA for three quarters of receptor subunits from a panel of non-glutamatergic/purinergic receptors were robustly expressed in WM glial cells, with some found at higher levels than in GM structures (Domingues et al, 2010). It seems likely that such wide-scale expression in glia, together with strong evidence for functional expression in some axons, is physiological, possibly in the same manner as described for glutamate and ATP.…”
Section: Atp and Adenosine Mediate Axonal Control Of Myelinationmentioning
confidence: 95%
“…In a recent study, Fern and colleagues found that mRNA for three quarters of receptor subunits from a panel of non-glutamatergic/purinergic receptors were robustly expressed in WM glial cells, with some found at higher levels than in GM structures (Domingues et al, 2010). It seems likely that such wide-scale expression in glia, together with strong evidence for functional expression in some axons, is physiological, possibly in the same manner as described for glutamate and ATP.…”
Section: Atp and Adenosine Mediate Axonal Control Of Myelinationmentioning
confidence: 95%
“…The potential sources of glutamate release to cerebral white matter include astrocytes, OLs, axons and cells of the choroid plexus. Mechanisms of glutamate release from axons (Kriegler and Chiu 1993; Stirling and Stys 2010) and astrocytes (Anderson and RA 2000; Bezzi et al 2004; Domingues et al 2010; Ye et al 2003) have been defined, while oligodendroglia express Na-dependent glutamate transporters and a X c − transporter, which are all potential sources of glutamate release during hypoxia-ischemia (Deng et al 2003; DeSilva et al 2009; DeSilva et al 2007; Domercq et al 1999; Fern and Moller 2000; Oka et al 1993). There is evidence for significant release of astrocytic glutamate in isolated immature rat optic nerve during in vitro modeled ischemia (Wilke et al 2004) as well as glutamate transport mechanisms in immature axons (Arranz et al 2008).…”
Section: Cellular-molecular Mechanisms Of Acute Wmimentioning
confidence: 99%
“…Astrocytes also release glutamate [69]. Loss of astrocyte glutamate homeostasis is a prerequisite for the excitotoxic cascade, a phenomenon that is becoming recognized in an increasing number of neurological disorders [70,71]. Zn 2+ may negatively modulate Ca 2+ mobilization in CA3 pyramidal cells after regional delivery of glutamate (1 mM) to the stratum lucidum, where mossy fibers exist, suggesting that Zn 2+ attenuates glutamate excitotoxicity through the action as a negative feedback factor (Fig.…”
Section: Zn 2+ Signaling In Glutamate Excitotoxicitymentioning
confidence: 99%